PEMIKIRAN PENDIDIKAN IBNU SINA DAN APLIKASINYA DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI INDONESIA - Utsman, Fathor Rachman (STAIN Pamekasan, 2010)
Abstract: An islamic leader who was delivering the most successful and monumental in controlling and developing several branches of science is Avicenna. He also examined education in several aspects, such as the human essence, the purposes of education, curriculum, teaching methods, and concepts of teacher. The applications of his thoughts were emphasizing on: the first, the importance of early childhood education; the second, the importance of moral education; the third, the urge of making education of al-Quran as a model; the fourth, soul -oriented education (an-nafs); and the fifth, the need to build non-dichotomy educational paradigm or integral education.